Представьте выражение в виде многочлена:1) (х^2-х+4)(х-5) 2) (2у-1)(у^2+5у-2)...

0 голосов
34 просмотров

Представьте выражение в виде многочлена:1) (х^2-х+4)(х-5)
2) (2у-1)(у^2+5у-2)
3)(2-3а)(-а^2+4а-8)
4) (3-4с)(2с^2-с-1)
5) (х^2-х+4)(2х^2-х+4)
6) (-5а^2+2а+3)(4а^2-а+1)
7) (8+4с)(2с^2-с-4)
8) (с-4)(с+2)(с+3).


Алгебра (42 баллов) | 34 просмотров
Дан 1 ответ
0 голосов

Решите задачу:

(2y-1)(y^2-5y-2)=2y^3-10y^2-4y-y^2+5y+2=2y^3-11y^2+y+2
 

(3-4c)(2c^2-c-1)=6c^2-3c-3-8c^3+4c^2+4c=-8c^3+10c^2+c-3
 

(c-4)(c+2)(c+3)=(c^2+2c-4c-8)(c+3)=c^3+3c^2-2c^2-6c-24=c^3+c^2-6c-24
 

(2-3a)(-a^2+4a-8)=-2a^2+8a-16+3a^3-12a^2+24a=3a^3-14a^2+32a-16
 

(x^2-x+4)(x-5)=x^3-5x^2-x^2+5x+4x-20=x^3-6x^2+9x-20  (x^2-x+4)(2x^2-x+4)=2x^4-x^3+4x-2x^3+x^2-4x+8x^2-4x+16=2x^4-3x^3+9x^2-4x+16
\\(-5a^2+2a+3)(4a^2-a+1)=-20a^4+5a^3-5a^2+8a^3-2a^2+2a+12a^2-3a+3=-20a^4+13a^3+7a^2-a+3
\\

(8+4c)(2c^2-c-4)=16c^2-8c-32+8c^3-4c^2-16c=8c^3+12c^2-24c-32
(4.6k баллов)